2005
DOI: 10.1246/cl.2005.862
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Luminescent Properties of Silver Nanoparticles Passivated by Fullerodendrons

Abstract: Spherical silver nanoparticles (diameter: 7–10 nm) were fabricated through passivation by fullerodendrons (C60(Gn-COOK) (n = 0.5, 1.5, 2.5)), which were synthesized from fullerene and anthracenyl focal poly(amido amine) dendrons with carboxylate terminals and different generations (G). The resultant nanocomposites presented unique luminescence, which was contributed by not only anthracenyl moiety but also poly(amido amine) dendron moiety, although the latter has no traditional fluorophore. Furthermore, fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…In our previous work, it was also found that different kinds of dendrimers with tertiary amine branching points could emit strong fluorescence by adjusting pH value [34]. Furthermore, we observed that fluorescence emitted from PA-MAM dendrimers or fullerodendrons was obviously affected by nanoparticles [35,36]. Because PAMAM dendrimers are a kind of organic molecules without traditional fluorophores, observations of the fluorescence were unexpected and attracted much attention.…”
Section: Introductionmentioning
confidence: 83%
“…In our previous work, it was also found that different kinds of dendrimers with tertiary amine branching points could emit strong fluorescence by adjusting pH value [34]. Furthermore, we observed that fluorescence emitted from PA-MAM dendrimers or fullerodendrons was obviously affected by nanoparticles [35,36]. Because PAMAM dendrimers are a kind of organic molecules without traditional fluorophores, observations of the fluorescence were unexpected and attracted much attention.…”
Section: Introductionmentioning
confidence: 83%
“…10 A mixture of C 60 (30 mg, 0.04 mM) and dendron (2) (70 mg, 0.08 mM) in 3 ml of o-dichlorobenzene was stirred at 45°C for four days under a nitrogen atmosphere. The initial purple color of the solution, due to unreacted C 60 , became red as the reaction proceeded.…”
Section: Synthesis Of Fullerodendrimer (1)mentioning
confidence: 99%
“…9 Recently we have reported a facile synthesis of fullerodendron, of which fullerene moiety is proved to be efficient photosensitizer to generate singlet oxygen. 10 Despite the many studies focused on fullerodendrimer themselves, 11 very little has been determined about fullerodendrimermediated chemical transformations. Fullerodendrimer might be candidate molecule for photocatalyst because of versatile solubility introduced by dendritic substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the PAMAM dendrimers as a protector, metal and metalderivative nanoparticles with small size and narrow size distribution were synthesized. [1][2][3][4][5][6][7][8][9][10][11][12] Then the protection by PAMAM dendrimers may develop the advanced application of nanoparticles as medical materials like therapeutic reagents besides industrial materials.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the PAMAM dendrimers as a protector, metal and metalderivative nanoparticles with small size and narrow size distribution were synthesized. [1][2][3][4][5][6][7][8][9][10][11][12] Then the protection by PAMAM dendrimers may develop the advanced application of nanoparticles as medical materials like therapeutic reagents besides industrial materials.Water-dispersible gold and silver nanoparticles with small sizes (less than 10 nm) were synthesized by the reduction of metal ions in the presence of PAMAM dendrimers.3-9 While in almost of investigations, metal nanoparticles were reduced with the aid of reducer, gold and silver nanoparticles were prepared by reducing the metal salt in PAMAM dendrimer solutions under UV, X-ray, or laser irradiation or heating. 3,4,[6][7][8] Particle sizes and their dispersion in water depended on the generation of dendrimers and the mixing ratio of metal ion and dendrimer.…”
mentioning
confidence: 99%